Answer:
The answer is below
Step-by-step explanation:
The standard form of the equation of an ellipse with major axis on the y axis is given as:
![\frac{(x-h)^2}{b^2} +\frac{(y-k)^2}{a^2} =1](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-h%29%5E2%7D%7Bb%5E2%7D%20%2B%5Cfrac%7B%28y-k%29%5E2%7D%7Ba%5E2%7D%20%3D1)
Where (h, k) is the center of the ellipse, (h, k ± a) is the major axis, (h ± b, k) is the minor axis, (h, k ± c) is the foci and c² = a² - b²
Since the minor axis is at (37,0) and (-37,0), hence k = 0, h = 0 and b = 37
Also, the foci is at (0,5) and (0, -5), therefore c = 5
Using c² = a² - b²:
5² = a² - 37²
a² = 37² + 5² = 1369 + 25
a² = 1394
Therefore the equation of the ellipse is:
![\frac{x^2}{1369}+ \frac{y^2}{1394} =1](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E2%7D%7B1369%7D%2B%20%5Cfrac%7By%5E2%7D%7B1394%7D%20%3D1)
I think it should be an= 49x3^(n-1)
Answer: No, because P(F T) = P(F) • P(T)
Step-by-step explanation:
Answer:
8ac+3b-7a
Step-by-step explanation:
2ac+6ac+4b-b-7a=
31.5 hope it helps have a good day